1995
DOI: 10.1007/bf00033628
|View full text |Cite
|
Sign up to set email alerts
|

Site specific differentiation in metal tolerance in the midge Chironomus riparius (Diptera, Chironomidae)

Abstract: Site specific differentiation in metal tolerance in the midge, Chironomus riparius (Diptera: Chironomidae) Postma, J.F.; Kyed, M.; Admiraal, W. Published in: Hydrobiologia DOI:10.1007/BF00033628 Link to publicationCitation for published version (APA): Postma, J. F., Kyed, M., & Admiraal, W. (1995). Site specific differentiation in metal tolerance in the midge, Chironomus riparius (Diptera: Chironomidae). Hydrobiologia, 315, 159-165. DOI: 10.1007/BF00033628 General rightsIt is not permitted to download or to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 28 publications
0
37
1
Order By: Relevance
“…It is clear that the response of C. riparius to a toxicant in polluted river water is di!erent from the response to similar toxicant levels in reference water. In EGD 1 water growth inhibition was only 15% while, based on the results of Postma et al (1995), an inhibition of 93% was expected (when assuming concentration additivity of zinc and cadmium).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…It is clear that the response of C. riparius to a toxicant in polluted river water is di!erent from the response to similar toxicant levels in reference water. In EGD 1 water growth inhibition was only 15% while, based on the results of Postma et al (1995), an inhibition of 93% was expected (when assuming concentration additivity of zinc and cadmium).…”
Section: Resultsmentioning
confidence: 92%
“…2, darkshaded bars) was determined by calculating a dose}re-sponse relationship for both metals according to Haanstra et al (1985). The larvae used by Postma et al (1995) originated from the same laboratory culture as the larvae used in the present study, and the experimental setup is similar to that of Postma et al (1995). It is clear that the response of C. riparius to a toxicant in polluted river water is di!erent from the response to similar toxicant levels in reference water.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…30 Some studies have demonstrated that cadmium, in high concentrations in the aquatic environment, causes changes in the growth of some insects, as larvae of Chironomus riparius. 31 Some researchers as 32 studying in forested and in impacted streams, pointed that aquatic insetcs as mayflies accumulate higher concentrations of Cd than caddisflies and stoneflies.…”
Section: Discussionmentioning
confidence: 99%